2000
DOI: 10.1016/s0378-1127(99)00270-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of land use practices to surface water quality in the Upper Oconee Watershed of Georgia

Abstract: On a watershed scale, geospatial information can be used to identify water resources that are least buffered from contamination. Implementing conservation practices at these locations may accelerate the process of increasing a watershed's ability to support its designated uses. The Upper Oconee Watershed of Georgia contains land areas devoted to poultry, dairy, and beef production. Within these historically agricultural lands, urbanization is proceeding rapidly around existing cities. Agricultural production p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 0 publications
8
90
2
3
Order By: Relevance
“…Thus, efforts within the watershed should be focused to develop a planning process in which agriculture and urban interests with responsibility for water quality are shared. Addressing these issues together is essential to avoid short-term counterproductive conflicts and to develop a long-term vision for the watershed (Fisher et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, efforts within the watershed should be focused to develop a planning process in which agriculture and urban interests with responsibility for water quality are shared. Addressing these issues together is essential to avoid short-term counterproductive conflicts and to develop a long-term vision for the watershed (Fisher et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of AN is related to the influence of domestic waste and agricultural runoff (Fisher et al 2000;Osborne and Wiley 1988). McFarland and Hauck (1999), in their study, found that higher nitrogen levels were detected in agricultural waters, where fertilizers, manure, and pesticide have been applied.…”
Section: Lpsmentioning
confidence: 99%
“…Poultry Litter Fertilization Impacts on Soil, Plant, and Water Characteristics in Loblolly Pine (Pinus taeda L.) Plantations and Silvopastures in the Mid-South USA 45 of N and P in surface water and eutrophication of water bodies have been found in areas with high levels of confined poultry and other animal production (Daniel et al, 1998;Sharpley, 1999;Fisher et al, 2000). State and federal environmental protection agencies have responded to these environmental concerns by implementing regulations requiring poultry operations to develop nutrient management plans, which will frequently reduce the allowable amounts of litter that can be applied .…”
Section: Elementmentioning
confidence: 99%